Nursing patient record practice and associated factors among nurses working in North Shewa Zone public hospitals, Ethiopia - Tadese, Mesfin; Endale, Agizew; Asegidew, Wondwosen; Tessema, Saba Desta; Shiferaw, Wondimeneh Shibabaw (Frontiers in Health Services, 2024)
Background: Nursing documentation is an essential component of nursing practice and has the potential to improve patient care outcomes. Poor documentation of nursing care activities among nurses has been shown to have negative impacts on health care quality. Objective: To assess the nursing documentation practice and its associated factors among nurses working in North Shewa Zone public hospitals, Ethiopia. Method: Institution-based cross-sectional study was conducted at North Shewa Zone public hospitals. A simple random sampling technique was used to select 421 nurses. A pre-tested, structured, self-administered questionnaire was used to gather the data. Data were entered into Epi Data version 3.1, and SPSS version 25 was used for further analysis.Binary logistic regressions were performed to identify independent predictors of nursing documentation practice. Adjusted odds ratio was calculated and p-value less than 0.05 with 95% CI was considered as statistically significant. Result: A total of 421 respondents took part, giving the survey a 100% response rate. The overall good practice of nursing care documentation was 51.1%, 95% CI (46.6, 55.8). In addition, 43.2%, 95% CI (38.5, 48.0) and 35.6%, 95% CI (30.9, 40.1) of nurses had good knowledge of and favorable attitudes toward nursing care documentation.Availability of operational standard for nursing documentation (AOR = 1.76; 95% CI: 1.18, 2.64), availability of documenting sheet (AOR = 1.51; 95% CI: 1.01, 2.29), and monitoring system (AOR = 1.61; 95%CI: 1.07, 2.41) were significantly associated with nursing care documentation practice.Nearly half of nursing care was not documented. The practice of nursing care documentation was significantly influenced by the availability of operational standards, documenting sheets, and monitoring systems. To improve the documentation practice, a continuous monitoring system and access to operational standards and documenting sheets are needed.